Complex Terrain Megacities and the Changing Character of Urban Operations - Jensen, Benjamin M.; Breitenbach, Henrik; Valeriano, Brandon (Marine Corps University Press (MCUP), 2019)
This edited volume, composed by military professionals in the Gray Scholars Program at Marine Corps University, describes the changing character of urban operations. The pattern of human settlement and interaction is changing and the future is urban. Because the majority of the world's population lives within cities, the future of strategic competition and conflict reside there as well. The density and connectivity of urban environments create a new type of complex terrain. Interests change from neighborhood to neighborhood, often intersecting global, political, and economic networks. Each city block sees shifting allegiances that often seem unclear from the outside. The cityscape compresses time and space while increasing uncertainty and complicating the conduct of military operations.